The Association of Patani Students (Southern Thailand) in Indonesia (HMPI) Jember Regency 2014-2022 - Hayiloh, Chesuraida; Swastika, Kayan; Pratama, Akhmad Ryan; Na'im, Mohamad; Kesuma Puja, Ngurah Ary; Nurul Jamil, Robit (History Education, University of Jember, 2024)
This thesis discusses the Patani (Southern Thailand) Student Association in Indonesia (HMPI) Jember Regency 2014-2022. The problem in this thesis is, What is the history of the establishment of the Patani Student Association (South Thailand) in Indonesia (HMPI) Jember Regency in 2014?, What are the dynamics of the Patani Student Association (South Thailand) in Indonesia (HMPI) Jember Regency 2014-2022? The method used in this research is the historical method, namely with stages in the form of Heuristics, Criticism, Interpretation and Historiography. The approach used is the Organizational Sociology Approach. The theory used is the theory of sosial institutions. Results and Discussion The background to the founding of HMPI is that it began with the unofficial establishment of a predecessor organization in the form of KMTJ (Thai Student Family in Jember) in 2011. The figures who initiated the founding of HMPI were Yasir bin Ahmad, Abdullah bin Muhammad Zainun, Sareef bin Ahmad, and Arkom bin Abdurrahman. Then KMTJ changed its name to KMPI (Patani (South Thailand) Student Family in Indonesia). The dynamics of HMPI Jember for 2014-2022 include several dynamic developments in HMPI such as changes to the symbol and flag in the 2015-2016 period. The number of HMPI members experiences growth each year, especially in 2015 as many as 46 new members joined HMPI. Then in 2020 there were no additional members due to the Covid-19 pandemic. HMPI programs generally include programs to improve the competence of Patani students. Keywords: Organization, HMPI, Development.